Determinants of Intellectual Capital Disclosure: An Investigation on DS30 Firms in Bangladesh - Dey, Pappu Kumar; Faruq, Mohammad Omar (Asian Journal of Accounting Perspectives, 2019)
Research aim: The study aims to investigate intellectual capital disclosure (ICD) practices and its determinants in Bangladesh. Design/Methodology/Approach: The top 30 firms known as DS30 companies that reflect around 51 percent of the total equity market capitalisation have been considered as a sample. Content analysis is used to extract the data from the annual report of the respective firm for the years 2013 to 2017. Multiple regression analysis is performed to identify the determinants of ICD. Research findings: This paper finds that board independence and globally affiliated auditors have a substantial positive impact on ICD. In contrast, board gender diversity documents marginally significant negative association with ICD. However, our examination does not show any significant impact of board size, leverage, profitability and firm size on ICD quality. Theoretical contribution/ Originality: This study differs in its approach of narrowing down the items of ICD index to maintain the perspective of a developing country like Bangladesh. It is a longitudinal study and does not consider any particular industry of Bangladesh to identify the drivers of ICD. Practitioner/ Policy implication: Policymakers and regulators could consider the factors identified in this paper for setting corporate reporting regulations, particularly corporate governance mechanisms. Research limitation: This study considered only the top 30 firms and 30 disclosure items. Our investigation is limited to only the annual reports of the respective companies. Keywords: Bangladesh, DS30 Companies, Determinants, Human Capital, Intellectual Capital Type of Manuscript: Research paper JEL Classification: M41, M49